G Protein-Coupled Receptors in Osteoarthritis: A Novel Perspective on Pathogenesis and Treatment - Wen, Ze-qin; Liu, Di; Zhang, Yi; Cai, Zi-jun; Xiao, Wen-feng; Li, Yu-sheng (Frontiers in Cell and Developmental Biology, 2021)
G protein-coupled receptors (GPCRs) are transmembrane receptor proteins that trigger numerous intracellular signaling pathways in response to the extracellular stimuli. The GPCRs superfamily contains enormous structural and functional diversity and mediates extensive biological processes. Until now, critical roles have been established in many diseases, including osteoarthritis (OA). Existing studies have shown that GPCRs play an important role in some OA-related pathogenesis, such as cartilage matrix degradation, synovitis, subchondral bone remodeling, and osteophyte formation. However, current pharmacological treatments are mostly symptomatic and there is a paucity of disease-modifying OA drugs so far. Targeting GPCRs is capable of inhibiting cartilage matrix degradation and synovitis and up-regulating cartilage matrix synthesis, providing a new therapeutic strategy for OA. In this review, we have comprehensively summarized the structures, biofunctions, and the novel roles of GPCRs in the pathogenesis and treatment of OA, which is expected to lay the foundation for the development of novel therapeutics against OA. Even though targeting GPCRs may ameliorate OA progression, many GPCRs-related therapeutic strategies are still in the pre-clinical stage and require further investigation.